2012
DOI: 10.1186/2045-824x-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative benefit for the combination of rapamycin and imatinib in tuberous sclerosis complex neoplasia

Abstract: Tuberous sclerosis (TS) is a common autosomal-dominant disorder characterized by tumors of the skin, lung, brain, and kidneys. Monotherapy with rapamycin however resulted in partial regression of tumors, implying the involvement of additional pathways. We have previously implicated platelet-derived growth factor-BB in TS-related tumorigenesis, thus providing a rationale for a combination of mTOR/PDGF blockade using rapamycin and imatinib. Here, we test this combination using a well-established preclinical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…46 The effect of exosomes on neo-angiogenesis is abrogated by the tyrosine kinase inhibitors, imatinib and dasatinib. 46 Given that imatinib was also shown to have more profound effect on Tsc2-null cell proliferation and tumor growth when combined with rapamycin in a mouse model of cutaneous tumorigenesis, 47 it is likely that the inhibitory effect of imatinib on exosome production is responsible for this result, therefore provides a rationale for combined therapy in TSC.…”
Section: Discussionmentioning
confidence: 97%
“…46 The effect of exosomes on neo-angiogenesis is abrogated by the tyrosine kinase inhibitors, imatinib and dasatinib. 46 Given that imatinib was also shown to have more profound effect on Tsc2-null cell proliferation and tumor growth when combined with rapamycin in a mouse model of cutaneous tumorigenesis, 47 it is likely that the inhibitory effect of imatinib on exosome production is responsible for this result, therefore provides a rationale for combined therapy in TSC.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous clinical study research found that rapamycin compounds could reduce the angiomyolipomata volume in TSC patients [43,44]. Interestingly, preclinical work suggests that a combination therapy of imatinib and rapamycin has more antitumor effect compared to rapamycin alone in an in vivo model of cutaneous tumorigenesis [45]. This improved effect could relate to the fact that tyrosine kinase inhibitors such as imatinib and dasatinib possess an inhibitory effect on EV production [46].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship between mTOR activation and PDGFRβ levels in TSC-derived cells has also been shown [146]. In a preclinical model, nearly complete tumour inhibition with a combination of rapamycin and imatinib targeting two distinct signalling pathways (mTORC1 and PDGFRβ, respectively) has been observed, suggesting a rationale for the clinical use of this combination therapy for TSC and LAM [147].…”
Section: Future Treatmentsmentioning
confidence: 96%